Effect of exercise-induced dehydration on endurance performance: evaluating the impact of exercise protocols on outcomes using a meta-analytic procedure - Goulet, E. D. B. (British Journal of Sports Medicine, 2013)
Objective It is purported that exercise-induced dehydration (EID), especially if >= 2% bodyweight, impairs endurance performance (EP). Field research shows that athletes can achieve outstanding EP while dehydrated > 2% bodyweight. Using the meta-analytic procedure, this study compared the findings of laboratory-based studies that examined the impact of EID upon EP using either ecologically valid (EV) (time-trial exercise) or non-ecologically valid (NEV) (clamped-intensity exercise) exercise protocols.